CONFLICT TRANSFORMATION BETWEEN BALINESE AND LAMPUNG ETHNIC IN REALIZING SUSTAINABLE PEACE IN BALINURAGA VILLAGE, WAY PANJI DISTRICT, LAMPUNG SELATAN REGENCY - Akbar Kurniadi; Tri Legionosuko; Wibisono Poespitohadi (Indonesia Defense University, 2019)
This article analyses the various factors that caused latent conflict in Balinuraga to be manifest conflict, also how conflict transformation is carried out to change conflictual conditions to be harmonious, destructive to constructive. Indonesian Survey Circle (LSI) noted that Lampung entered into five (5) regions with the worst levels of discrimination after the reformation. So, the researcher feels the need to raise the theme of conflict transformation in Balinuraga as the title and subject matter of this paper. This research was conducted using qualitative methods by collecting data through interviews, observation and documentation. The researcher used several theories and concepts, such as Conflict Theory, Conflict Transformation Theory, Cooperation Theory, Social Identity Theory, ABC Triangle Concept Galtung Conflict, SAT Concept, and Peace Concept. The results showed that conflict in Balinuraga was triggered by juvenile delinquency, extended with the issue of ethnicity and arrogance between groups as an accelerator, and was motivated by transmigration policies and the issue of economic inequality as structural factors. Conflict transformation efforts are carried out in four dimensions, namely personal, relational, cultural, and structural in order to realize sustainable peace and national security.Keywords: conflict, conflict transformation, ethnicity, culture, and peace